Pedagogical strategy to reinforce (or increase) thinking skills in university students - Molina, Mónica
The research applies a pedagogical strategy that strengthens the exercise of thought operations exposed in the third of the Marzano’s dimensions, (1992), Known as "Thought related to the refinement and deepening of knowledge".   A quasi-experimental design with 54 subjects is used, applying pre-test and post-test allowing comparison of the strategy’s effect. The results are reported based on eight workshops presented as developing the thinking skills used by students.   Workshops are evaluated through which, through theory and exemplification, students are led to understand text readings that correspond to a fifth semester course of the Psychology and Nursing Programs.   Significant differences between the pre-test and post-test of the two programs were found in the data obtained; in psychology from 6.17 to 8.0 and in nursing from 5.62 and 6.60 in an academic period.   In conclusion, this proposal could be applied to other subjects in the curriculum of other career courses and university institutions, to strengthen/reinforce thinking skills and improve academic performance